Life‐Cycle Variations in the Association between Current and Lifetime Income: Replication and Extension for Sweden - Böhlmark, Anders; Lindquist, Matthew J. (Journal of Labor Economics, 2006)
We apply Haider and Solon’s generalized errors‐in‐variables model to Swedish income tax data to produce estimates of the association between current and lifetime income. Our estimates demonstrate strong life‐cycle patterns. This implies that the widespread use of current income as a proxy for lifetime income leads to inconsistent parameter estimates (i.e., life‐cycle bias) even when the proxy is used as the dependent variable. Estimates for comparable cohorts of Swedish and American men demonstrate surprising similarities. There are, however, significant gender and cohort differences in this association that lead to statistically significant and quantitatively meaningful differences in life‐cycle biases.